Projective Approximation of Double Limit Points for Nonlinear Problems (Journal of Computational Mathematics, 1990)
In [2], general approximation results for the solution in a neighborhood of a simple limit point are given. In this paper we give projective approximation results for the solutions in a neighborhood of a double limit point. Application of these results to a nonlinear partial differential equation and numerical results are given.